Creating Better Action Plans for Writing Tasks via Vocabulary-Based Planning - Kaur, Harmanpreet; Williams, Alex; Thompson, Anne Loomis; Lasecki, Walter; Iqbal, Shamsi; Teevan, Jaime (Computer-Supported Cooperative Work (CSCW), 2018)
While having a step-by-step breakdown for a task—an action plan—helps people complete tasks, prior work has shown that people prefer not to make action plans for their own tasks. Getting planning support from others could be beneficial, but it is limited by how much domain knowledge people have about the task and how available they are. Our goal is to incorporate the benefits of having action plans in the complex domain of writing, while mitigating the time and effort costs of creating plans. To mitigate these costs, we introduce a vocabulary—a finite set of functions pertaining to writing tasks—as a cognitive scaffold that enables people with necessary context (e.g. collaborators) to generate action plans for others. We develop this vocabulary by analyzing 264 comments, and compare plans created using it with those created without any aid, in an online study with 768 comments(N = 145) and a lab study with 96 comments (N = 8). We show that using a vocabulary reduces planning time and effort and improves plan quality compared to unstructured planning, and opens the door for automation and task sharing for complex tasks.